PENGARUH PEMBERIAN CACING SUTERA (Tubifex sp.) DAN KEONG SAWAH (Pila ampullacea) TERHADAP PERTUMBUHAN IKAN PATIN (Pangasius sp.) The Influence of Application Silkworm (Tubifex sp) and Snails (Pila ampullacea) to the Growth of Patin (Pangasius sp) - Muhammad Hilman Zarkasih; Eriyusni Eriyusni; Rusdi Leidonald (AQUACOASTMARINE, 2015)
Patin is a famous fresh water fish that have high economic value in Indonesia. This research was conducted to study the influence of the application of silkworm (Tubifex sp.) and Snails (Pila ampulacea) to patin (Pangasius sp.) growth. This research was conducted on November-January of 2015 in Binjai. The statistical result show significance different between silkworm and snail (p<0.01).The absolute average weight of growth of the fish with the application of snails is 7.55 g, and with the silkworm is 8.89 g. The absolute length on the snail treatment is 3.36 cm and with the silkworm is 3.89 cm. The daily growth rate on the 70 th day age on snail and silkworm is 0.188 g and 0.213 g, while the higher specific growth rate to the snail and silkworm is 0.026% and 0.027%, Efficiency of fish feed with snail and silkworm is 0.381 g and 0.403 g. Keywords : Pangsasius sp., Growth, Silkworm (Tubifex sp.), Snails (Pila ampullaceae).